2008
DOI: 10.1373/clinchem.2008.107615
|View full text |Cite
|
Sign up to set email alerts
|

Snapback Primer Genotyping with Saturating DNA Dye and Melting Analysis

Abstract: Background: DNA hairpins have been used in molecular analysis of PCR products as self-probing amplicons. Either physical separation or fluorescent oligonucleotides with covalent modifications were previously necessary. Methods: We performed asymmetric PCR for 40–45 cycles in the presence of the saturating DNA dye, LCGreen Plus, with 1 primer including a 5′ tail complementary to its extension product, but without any special covalent modifications. Samples were amplified either on a carousel Ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 39 publications
2
46
0
Order By: Relevance
“…D: The snapback primer design only requires two primers, one with a 5Ј extension that is complementary to its own extension product. 39 Asymmetric PCR overproduces one strand, so that both full-length PCR product (amplicon) and an excess of one strand are formed. The excess single strand snaps back on itself (dotted line) so that its complementary regions (light gray lines) anneal to form a hairpin stem.…”
Section: Reducing Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…D: The snapback primer design only requires two primers, one with a 5Ј extension that is complementary to its own extension product. 39 Asymmetric PCR overproduces one strand, so that both full-length PCR product (amplicon) and an excess of one strand are formed. The excess single strand snaps back on itself (dotted line) so that its complementary regions (light gray lines) anneal to form a hairpin stem.…”
Section: Reducing Complexitymentioning
confidence: 99%
“…39 Such snapback primers form intramolecular hairpins (similar to the more complicated Scorpion primers) and allow genotyping by melting. With snapback primers, only two unlabeled oligonucleotides are necessary and 3Ј-blocking is not required ( Figure 3D).…”
mentioning
confidence: 99%
“…[36][37][38] However, several strategies can be used to achieve better resolution: genotyping using small amplicons, unlabelled probes, snapback primers, internal temperature calibrators and/or mixing patient samples with the reference control genotype. [39][40][41][42][43][44] We used internal calibrators and DNA mixing to improve the resolution of individual genotypes for four amplicons of the COX genes. However, the majority of examined amplicons did not require these adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…HRMA can effectively distinguish between different alleles and genotypes at single nucleotide polymorphism (SNP) loci (13,15,16). To date, three novel methods have been developed for HRMA: The small-fragment amplification method (17), the non-labeled probe method (18) and the snapback probe primer method (19). A recent study showed that the method of genomic DNA extraction influences the polymerase chain reaction (PCR)-HRMA product (20).…”
Section: Introductionmentioning
confidence: 99%